Berenstain Bears (The) / : Grow-it!: Mother nature has such a green thumb - Berenstain, Stan (New York : Random House, 1996)
As brother and sister help Mama plant a seeds in the garden, they discover the importance of seeds and how they become useful and important plants.
Keywords: Seeds-Fiction; Bears-Fiction; Plants-Fiction; Gardening-Fiction